Thermoregulatory and perceptual effects of a percooling garment worn underneath an American football uniform - Keen, M. L.; Miller, K. C.; Zuhl, M. N. (The Journal of Strength and Conditioning Research, 2017)
American football athletes are at the highest risk of developing exertional heat illness (EHI). We investigated whether percooling (i.e., cooling during exercise) garments affected perceptual or physiological variables in individuals exercising in the heat while wearing football uniforms. Twelve male participants (age = 24 ± 4 year, mass = 80.1 ± 8.5 kg, height = 182.5 ± 10.4 cm) completed this cross-over, counterbalanced study. On day 1, we measured peak oxygen consumption (VO2). On days 2 and 3, participants wore percooling garments with (ICE) or without (CON) ice packs over the femoral and brachial arteries. They donned a football uniform and completed 3, 20-minute bouts of treadmill exercise at ~50% of peak VO2 (~33° C, ~42% relative humidity) followed by a 10-minute rest period. Ice packs were replaced every 20 minutes. Rating of perceived exertion (RPE), thermal sensation, and thirst sensation were measured before and after each exercise bout. Environmental symptoms questionnaire (ESQ) responses and urine specific gravity (Usg) were measured pretesting and after the last exercise bout. VO2, change in heart rate (dHR), and change in rectal temperature (dTrec) were measured every 5 minutes. Sweat rate, sweat volume, and percent hypohydration were calculated. No interactions (F 17,187 = 1.6, p = 0.1) or main effect of cooling condition (F 1,11 = 1.4, p = 0.26) occurred for dTrec, dHR, thermal sensation, thirst, RPE, ESQ, or Usg. No differences between conditions occurred for sweat volume, sweat rate, or percent hypohydration (t11 = 0.7, p = 0.25). VO2 differed between conditions over time (F 15,165 = 3.3, p < 0.001); ICE was lower than CON at 30, 55, and 70 minutes (p = 0.05). It is unlikely that these garments would prevent EHI or minimize dehydration in football athletes.